Too-Much-of-a-Good-Thing effect of Prosocial Silence and Voice - Shahjehan, Asad; Yasir, Muhammad (Makara Human Behavior Studies in Asia, 2017)
This study assesses the effects of prosocial silence and voice on organizational citizenship behaviors directed towards individuals under the “Too-Much-of-a-Good-Thing” theory. It is assumed that greater prosocial silence and voice lead to organizational citizenship. However, the theory of too-much-of-a-good-thing suggests that extreme behaviors may perversely have a negative effect raising the possibility that the relationship is curvilinear rather than linear. A similar nonlinear relationship is suggested in this study. Standardized measures of prosocial voice, prosocial silence and organizational citizenship were collected from 381 faculty members from three mid-cycle universities. Regression analyses revealed a significant curvilinear (an inverted U-Shaped) relationship between prosocial voice and organizational citizenship and likewise prosocial silence and organizational citizenship. Too little and, similarly, too much prosocial voice and silence were associated with worse organizational citizenship.